Characterization of Soil Heavy Metal Pollution in a Mining Area in Southwest Yunnan - Li, Yingmei; Shang, Xiaoyan; Luo, Zhaojie (International Journal of Social Sciences and Public Administration, 2025)
This study takes a mining area in southwest Yunnan Province of China as the research object to study the pollution of heavy metals as, cadmium and mercury in the soil of a mining area in Jingdong County, Puer City, Yunnan Province. The single factor index method is used to calculate the multiple of cadmium, mercury and arsenic in each soil layer under different pH values in the mining area, and the Nemerol pollution index method is used to study the pollution characteristics. The results showed that the soil pollution degree of S4 soil layer at 50~150cm and the surface soil of S7 detection point reached the warning line; However, the soil pollution at other detection points and at different soil levels showed slight pollution. The conclusion shows that there is slight pollution in the soil within the assessment range, which needs attention and measures should be taken to reduce the risk of heavy metal pollution in the soil of the mining area.